Simple aminobenzoic acid promoted palladium catalyzed room temperature Suzuki–Miyaura cross-coupling reaction in aqueous media. Issue 22 (27th May 2015) - Sarmah, Gayatri; Bora, Utpal
Graphical abstract: Abstract: A highly efficient catalytic system based on Pd(OAc)2 and 4-aminobenzoic acid has been developed for the room temperature Suzuki–Miyaura cross-coupling reaction in aqueous media. The system can tolerate a wide range of functionalized arylboronic acids and aryl halides. Furthermore, this protocol is also applicable for hetero-aryl bromides and hetero-arylboronic acids.